2020
DOI: 10.1155/2020/2683753
|View full text |Cite
|
Sign up to set email alerts
|

Decreased Soluble Receptor of Advanced Glycation End Product Levels Correlated with Inflammation in Silicosis

Abstract: Silicosis is a devastating disease caused by inhalation of silica dust that leads to inflammatory cascade and then scarring of the lung tissue. Increasing evidences indicate that soluble receptor for advanced glycation end products (sRAGE) is involved in inflammatory diseases. However, no data on the possible relationship between sRAGE and inflammation of silicosis are available. In this study, serum from subjects with silicosis (n=59) or from healthy controls (HC, n=14) was analyzed for the secretion of sRAGE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Alveolar macrophage is the primary immune cell that recognizes and engulfs silica particles (Leung et al, 2012;Mossman and Churg, 1998). Macrophages activated by silica particles demonstrate enhanced pro-inflammatory cytokine production, including interleukin (IL)-1β, tumor necrosis factor-α (TNF-α) and IL-6, which play central roles in the inflammatory response and the accumulation of lung collagen (Piguet et al, 1990;Tripathi et al, 2010;Liu et al, 2020). In animal models, suppressing pro-inflammatory cytokine pro-duction effectively inhibited silica-induced inflammation, even the fibrotic responses (Di Giuseppe et al, 2009;Guo et al, 2013;Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Alveolar macrophage is the primary immune cell that recognizes and engulfs silica particles (Leung et al, 2012;Mossman and Churg, 1998). Macrophages activated by silica particles demonstrate enhanced pro-inflammatory cytokine production, including interleukin (IL)-1β, tumor necrosis factor-α (TNF-α) and IL-6, which play central roles in the inflammatory response and the accumulation of lung collagen (Piguet et al, 1990;Tripathi et al, 2010;Liu et al, 2020). In animal models, suppressing pro-inflammatory cytokine pro-duction effectively inhibited silica-induced inflammation, even the fibrotic responses (Di Giuseppe et al, 2009;Guo et al, 2013;Sato et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…A meta-analysis for each of the three cytokines was performed. The publication dates for the studies used in the meta-analysis ranged from 1994 to 2021 (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). In total, the 11 studies combined were comprised of 547 control (healthy) participants and 938 patients with pneumoconiosis.…”
Section: Resultsmentioning
confidence: 99%
“…Studies found that TNF-α and IL-6 were increased in the serum [ 27 ] and BALF [ 28 ] of patients with silicosis. TGF-β1 and CTGF, two classical pro-fibrotic cytokines, were also found to increase in serum of patients with silicosis and lung tissues of silicotic rat [ 29 31 ]. Similarly, our study found that the secretion of serum TGF-β1, CTGF, TNF-α and IL-6 were higher in patients with silicosis than in healthy subjects.…”
Section: Discussionmentioning
confidence: 99%